SOSIALISASI PENCEGAHAN STUNTING MELALUI EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT DI KELURAHAN KELAYU JORONG - Vitri, Desy Aryanti Pardilla; Akbari, Gilang Zulfa; Yasmin, Yasmin; Afdhalu, Ahmad Naufal; Artapati, Lalu; Insan, Rofi Akhlakul; Yanti, Arnita; Nada, Lisa Katun; Rijal, Siti Khairun Hafizo; Ardira, Rizki Desima (Jurnal Wicara, 2024)
Stunting is a condition where a child's physical state, especially height, differs from other children of the same age. Stunting can occur in children starting from the womb due to insufficient nutritional intake or infectious diseases. Kelayu Jorong Subdistric is one of the areas in East Lombok that is currently addressing the issue of stunting, based on survey information obtained on November 29, 2023. Therefore, through the Community Empowerment Real Work Lecture (KKN PMD) activity by Mataram University, a socialization activity is being carried out as an initial step to address and prevent stunting incidents in Kelayu Jorong Subdistric. The methods implemented include: 1) Conducting a census of the number of children experiencing stunting, 2) Monitoring stunting, 3) Socialization with implementation consisting of preparation and determination of target targets, making and sending letters, preparing event and activity equipment, and implementing socialization on stunting management at the office of Kelayu Jorong Subdistric. The results obtained show that in Kelurahan Kelayu Jorong, a total of 17 children are experiencing stunting. Based on information obtained from the community leader and interviews with several mothers who have stunted children, it is known that the community in Kelayu Jorong gets water from wells and often the water is not boiled before consumption. Therefore, socialization activities are carried out with the theme of clean and healthy living behavior as a preventive and treatment effort. This socialization activity receives enthusiasm from the community. This activity can provide understanding to the community about the importance of maintaining a balanced diet and clean and healthy living behavior, with the hope that the health level of children in Kelayu Jorong Subdistrict can be improved.